Feasibility Study on Application of Seawater Flue Gas Desulfurization (SWFGD) in Ultra-low Emission (ULE). (January 2019) - Yao, Che; Li, Tao; Yanhua, Zhou; Hong, Zhang; Yanming, Zhou
Abstract: As an economical and energy-saving environmental protection technology, seawater desulfurization technology is widely used in environmental protection facilities of coal-fired power plants. With the introduction of the ULE management, the traditional seawater desulfurization technology can no longer meet the increasingly stringent environmental requirements. Based on the theory of gas-liquid mass transfer and nozzle atomization size distribution analysis, this paper investigates the effect and limitation of desulfurization performance enhancement by adding spray layer. The research results show that the design efficiency of the fifth layer spray is only 31.94%, and the export SO2 is only reduced to 98mg/m 3 . The concentration level is far from the ULE standard (35mg/m 3 ), and the spray layer does not fully meet the requirements of ULE standards. Therefore, further considerations need to be taken from other ways of increasing efficiency.